Meretoja’s Syndrome: Lattice Corneal Dystrophy, Gelsolin Type - I. Casal; S. Monteiro; C. Abreu; M. Neves; L. Oliveira; M. Beirão (Case Reports in Medicine)
Lattice corneal dystrophy gelsolin type was first described in 1969 by Jouko Meretoja, a Finnish ophthalmologist. It is caused by an autosomal dominant mutation in gelsolin gene resulting in unstable protein fragments and amyloid deposition in various organs. The age of onset is usually after the third decade of life and typical diagnostic triad includes progressive bilateral facial paralysis, loose skin, and lattice corneal dystrophy. We report a case of a 53-year-old female patient referred to our Department of Ophthalmology by severe dry eye and incomplete eyelid closure. She had severe bilateral facial paresis, significant orbicularis, and perioral sagging as well as hypoesthesia of extremities and was diagnosed with Meretoja’s syndrome at the age of 50, confirmed by the presence of gelsolin mutation. At our observation she had bilateral diminished tear film break-up time and Schirmer test, diffuse keratitis, corneal opacification, and neovascularization in the left eye. She was treated with preservative-free lubricants and topical cyclosporine, associated with nocturnal complete occlusion of both eyes, and underwent placement of lacrimal punctal plugs. Ocular symptoms are the first to appear and our role as ophthalmologists is essential for the diagnosis, treatment, and monitoring of ocular alterations in these patients.